2021
DOI: 10.3390/life11101002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characterization of Clinical Fungal Isolates from Pauls Stradinš Clinical University Hospital, Latvia: A 4-Year Surveillance Report

Abstract: Nosocomial fungal infections are an emerging global public health threat that requires urgent attention and proper management. With the limited availability of treatment options, it has become necessary to understand the emerging epidemiological trends, mechanisms, and risk factors. However, very limited surveillance reports are available in the Latvian and broader European context. We therefore conducted a retrospective analysis of laboratory data (2017–2020) from Pauls Stradinš Clinical University Hospital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 125 publications
1
3
0
Order By: Relevance
“…K. pneumoniae was one of the major nosocomial pathogens in a Moscow neurosurgery ICU during the period from January 2014 to May 2019, causing about 28% infections including those of the central nervous system, bloodstream, respiratory tract, and urinary tract. This rate was similar to those in the Multispecialty Hospital, Riga, Latvia in 2017–2020 (16–20%) [ 11 ], and significantly lower than those reported from 15 China centers in 2012–2016 (52.4%) [ 12 ].…”
Section: Discussionsupporting
confidence: 82%
“…K. pneumoniae was one of the major nosocomial pathogens in a Moscow neurosurgery ICU during the period from January 2014 to May 2019, causing about 28% infections including those of the central nervous system, bloodstream, respiratory tract, and urinary tract. This rate was similar to those in the Multispecialty Hospital, Riga, Latvia in 2017–2020 (16–20%) [ 11 ], and significantly lower than those reported from 15 China centers in 2012–2016 (52.4%) [ 12 ].…”
Section: Discussionsupporting
confidence: 82%
“…All the starting materials and reagents were of analytical grade purchased from commercial sources (Alfa Aesar) and were used without further purification. 1 H NMR spectra were recorded (at NIPER Hyderabad) in solvent dimethyl sulfoxide (DMSO)-d6 using BRUKER AV 500MHz (Germany). Chemical shifts were reported in δ ppm with Tetramethylsilane as an internal standard (TMS, δ = 0.0).…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Candidiasis is mainly caused by Candida albicans. [1][2][3] Morphologically, is a versatile microbe that exists in three forms i.e. yeasts, pseudohyphae, and hyphae.…”
Section: Introductionmentioning
confidence: 99%
“…Also,Abbas et al (2017) reported 88% fungal contamination in 70 samples of pigeon faeces, 25 samples of domestic bird faeces, and 5 samples of chicken faeces.The findings of the present study showed that the faeces of different birds, including parrots, could be the habitat of pathogenic and opportunistic fungal species, including C. neoformans and Candida species, and cause their spread in the living environment of humans and animals. Since in recent years, the occurrence of cryptococcosis and other opportunistic systemic fungal infections in patients with immune system deficiency, including those with AIDS, has increased significantly(Jain et al, 2021), parrot droppings should be considered a source of danger for public health. Cryptococcus species especially C. neoformans and C. gatti cause illness in humans(Pakshir et al, 2018).The presence of C. neoformans in bird droppings is one of the possible routes of transmission of cryptococcosis to humans.…”
mentioning
confidence: 99%